2022
DOI: 10.3390/s22135020
|View full text |Cite
|
Sign up to set email alerts
|

DDQN with Prioritized Experience Replay-Based Optimized Geographical Routing Protocol of Considering Link Stability and Energy Prediction for UANET

Abstract: Unmanned aerial vehicles (UAVs) are important equipment for efficiently executing search and rescue missions in disaster or air-crash scenarios. Each node can communicate with the others by a routing protocol in UAV ad hoc networks (UANETs). However, UAV routing protocols are faced with the challenges of high mobility and limited node energy, which hugely lead to unstable link and sparse network topology due to premature node death. Eventually, this severely affects network performance. In order to solve these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Simulation was conducted for configuration parameters given in Table I. Comparison of proposed solution's performance is done against Q-learning based QoS routing proposed by Xinchen et al [ 24], link stability-based routing proposed by Zhang et al [21], trajectory aided OLSR routing proposed by Hou et al [7].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Simulation was conducted for configuration parameters given in Table I. Comparison of proposed solution's performance is done against Q-learning based QoS routing proposed by Xinchen et al [ 24], link stability-based routing proposed by Zhang et al [21], trajectory aided OLSR routing proposed by Hou et al [7].…”
Section: Resultsmentioning
confidence: 99%
“…Overhead has reduced in proposed solution, due to use of less maintenance overhead. Zhang et al [21] Xinchen et al [24] www.ijacsa.thesai.org V. DISCUSSION AND RESULTS…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, several existing solutions have tried utilizing SDN or a multi-objective routing for ground vehicles [ 10 , 11 , 12 ]. Moreover, routing in UAVs which considers metrics such as charging stations, VANET supporting networks, and trajectory-based systems has also been proposed [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. An exhaustive review of existing schemes identified that a routing scheme should not consider a single objective while disregarding its byproduct’s impact.…”
Section: Introductionmentioning
confidence: 99%